Nanodelivery of traditional Chinese Gingko Biloba extract EGb-761 and bilobalide BN-52021 induces superior neuroprotective effects on pathophysiology of heat stroke - Sahib S.; Sharma A.; Muresanu D.F.; Zhang Z.; Li C.; Tian Z.R.; Buzoianu A.D.; Lafuente J.V.; Castellani R.J.; Nozari A.; Patnaik R.; Menon P.K.; Wiklund L.; Sharma H.S. (My University, 2025)
Military personnel often exposed to high summer heat are vulnerable to heat stroke (HS) resulting in abnormal brain function and mental anomalies. There are reasons to believe that leakage of the blood-brain barrier (BBB) due to hyperthermia and development of brain edema could result in brain pathology. Thus, exploration of suitable therapeutic strategies is needed to induce neuroprotection in HS. Extracts of Gingko Biloba (EGb-761) is traditionally used in a variety of mental disorders in Chinese traditional medicine since ages. In this chapter, effects of TiO2 nanowired EGb-761 and BN-52021 delivery to treat brain pathologies in HS is discussed based on our own investigations. We observed that TiO2 nanowired delivery of EGb-761 or TiO2 BN-52021 is able to attenuate more that 80% reduction in the brain pathology in HS as compared to conventional drug delivery. The functional outcome after HS is also significantly improved by nanowired delivery of EGb-761 and BN-52021. These observations are the first to suggest that nanowired delivery of EGb-761 and BN-52021 has superior therapeutic effects in HS not reported earlier. The clinical significance in relation to the military medicine is discussed. © 2021 Elsevier B.V.